ARL8B mediates lipid droplet contact and delivery to lysosomes for lipid remobilization - Dilip Menon; Apoorva Bhapkar; Bhoomika Manchandia; Gitanjali Charak; Surabhi Rathore; Rakesh Mohan Jha; Arpita Nahak; Moumita Mondal; Mohyeddine Omrane; Akash Kumar Bhaskar; Lipi Thukral; Abdou Rachid Thiam; et al. (Cell Reports, 2023)
Summary: Lipid droplets (LDs) play a crucial role in maintaining cellular lipid balance by storing and delivering lipids as needed. However, the intricate lipolytic pathways involved in LD turnover remain poorly described, hindering our comprehension of lipid catabolism and related disorders. Here, we show a function of the small GTPase ARL8B in mediating LD turnover in lysosomes. ARL8B-GDP localizes to LDs, while ARL8-GTP predominantly favors lysosomes. GDP binding induces a conformation with an exposed N-terminal amphipathic helix, enabling ARL8B to bind to LDs. By associating with LDs and lysosomes, and with its property to form a heterotypic complex, ARL8B mediates LD-lysosome contacts and efficient lipid transfer between these organelles. In human macrophages, this ARL8B-dependent LD turnover mechanism appears as the major lipolytic pathway. Our finding opens exciting possibilities for understanding the molecular mechanisms underlying LD degradation and its potential implications for inflammatory disorders.